Simulating pumping equipment unit wear based on elastic and plastic deformations of surface nanoirnesses in a stated friction mode - Suslov, A. G.; Shalygin, M. G. (AIP conference proceedings, 2021)
The article proposes a model of the friction surface wear of pumping equipment involved in pumping oil and oil products at high temperatures. The applicability of the proposed dependencies is substantiated only for the period of steady-state wear. The general dependences of determining the wear of the surface nanogeometry in the stated mode and their constituent factors are presented. The analysis of the proposed provisions shows that the wear of nanogeometry depends to a greater extent on the deformation and adhesive components. The materials of the article can be used to determine the friction unit wear of oil pipeline pumping equipment, subject to elastic and plastic deformations.